2016
DOI: 10.1097/md.0000000000002874
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Epicardial Adipose Tissue Thickness With Adverse Cardiovascular Outcomes in Patients With Atrial Fibrillation

Abstract: The thickness of epicardial adipose tissue (EAT) was reported to be highly associated with the incidence and severity of atrial fibrillation (AF). This study was conducted to analyze the ability of EAT thickness in predicting adverse cardiovascular (CV) events in AF.In 190 persistent AF patients, we performed a comprehensive transthoracic echocardiographic examination with assessment of EAT thickness. The definition of CV events included CV mortality, hospitalization for heart failure, myocardial infarction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 46 publications
4
44
0
8
Order By: Relevance
“…The available evidence supports this pathophysiological framework. Epicardial adipose tissue is increased in patients with HFpEF and in those with AF, and is particularly prominent when HFpEF and AF coexist, particularly if patients have evidence of systemic inflammation or are at risk of adverse outcomes . Coronary microvascular dysfunction is exceptionally common in HFpEF and, when present, is associated with a two‐fold increase in the prevalence of AF .…”
Section: Pathophysiological Mechanisms Leading To Hfpefmentioning
confidence: 99%
“…The available evidence supports this pathophysiological framework. Epicardial adipose tissue is increased in patients with HFpEF and in those with AF, and is particularly prominent when HFpEF and AF coexist, particularly if patients have evidence of systemic inflammation or are at risk of adverse outcomes . Coronary microvascular dysfunction is exceptionally common in HFpEF and, when present, is associated with a two‐fold increase in the prevalence of AF .…”
Section: Pathophysiological Mechanisms Leading To Hfpefmentioning
confidence: 99%
“…В частности, эхокардиографически определяемая ТЭЖ изучалась в качестве предиктора ССО (сердечно-сосудистая смерть, госпитализация по поводу сердечной недо-статочности, инфаркт миокарда, мозговой инсульт) у пациентов с фибрилляцией предсердий (n=190, 67,4% мужчин, средний возраст 70 лет, длительность наблюдения составила в среднем 29 месяцев). По результатам многофакторного анализа, ТЭЖ, превышающая 6 мм (относительный риск 1,211, 95% ДИ 1,084-1,351, р<0,001), была ассоциирована с раз-витием сердечно-сосудистого события, при этом на каждый 1 мм ТЭЖ увеличение риска составило 1,224 (95% ДИ 1,096-1,368, р<0,001) [50].…”
Section: эпикардиальная жировая ткань: основные характеристики и метоunclassified
“…In one such study, an EAT thickness greater than 6 mm was associated with a significant reduction in cardiovascular event‐free survival . In the same study, EAT was also shown to correlate with CHA 2 DS 2 ‐VASc score, although this association appeared to be attenuated with the addition of further covariates . More recently, an increased EAT volume was reported in AF patients who developed stroke, and total EAT was as an independent predictor of excess risk of stroke occurrence after AF diagnosis .…”
mentioning
confidence: 91%
“…More recently, preliminary investigations are emerging regarding the possible relationship between visceral fat depots and AF‐related stroke. In one such study, an EAT thickness greater than 6 mm was associated with a significant reduction in cardiovascular event‐free survival . In the same study, EAT was also shown to correlate with CHA 2 DS 2 ‐VASc score, although this association appeared to be attenuated with the addition of further covariates .…”
mentioning
confidence: 91%